The Role of Organizational Commitment and Procedural Justice in Moderating the Relationship between Budgetary Participation and Managerial Performance - Murwaningsari, Etty (Gadjah Mada International Journal of Business, 2008)
The objective of this research is to identify the role of organizational commitment and procedural justice in moderating the relationship between budgetary participation and managerial performance. This research utilizes the mail survey method to collect primary data from September 2007 to mid-November 2007 by sending questionnaire forms to corporate managers involved in the budgeting process.The empirical result of this research indicates that budget participation has a positive and significant influence on managerial performance. The subsequent test finds that organizational commitment can strengthen the relation between budget participation and managerial performance. The last test shows that procedures have no influence on the relationship between budget participation and managerial performance.